El Aprendizaje Significativo Como Estrategia De Estimulación De La Escritura Del Idioma Inglés En Educación General Básica - Daniela Fernanda Guano Merino; Marcelo Eduardo Allauca Peñafiel; Enrique Jesús Guambo Yerovi; Luis Alberto Veloz Andrade (European Scientific Journal, ESJ, 2017)
The objective of the present investigation was the analysis of the use of strategies of significant learning in order to stimulate writing in the English language, which affect the development of the writing skill causing low performance and deficient level of knowledge in the students of sixth and seventh years of general basic education. The bibliographic information on significant learning sustains the importance of the use of didactic material in the processes of assimilation and interaction when acquiring educational skills and competences. They facilitate the connection to preexisting mental schematics in order to incorporate knowledge that generates significant learning. The methods used were deductive-inductive, documentary and applied bibliography, which allowed the collection of information through observation sheets. The results showed that the cognitive processes are inadequate due to lack of didactic material to develop and stimulate the writing of the English language. Due to this worksheets were designed and applied that contain grammatical structure, vocabulary, completion exercises, active memorization, spelling, word classification, sentence formation, short sentences and long with positive and negative answers; use of demonstrative adjectives, possessive pronouns, classification of nouns; all this to stimulate writing and a base of knowledge in the learning of English as a second language.